A MULTIPLEX PCR BASED METHOD FOR THE DETECTION OF AGRICULTURALLY IMPORTANT AFLATOXIGENIC AND OCHRATOXIGENIC FUNGAL SPECIES FROM CEREALS - K. VENKATA REDDY; S.R. PRIYANAKA; I. BHASKAR REDDY (International Journal of Pharma and Bio Sciences, 2013)
A total of 112 isolates were recovered from cereal grains collected from 10 districts of Tamilnadu and Andhra Pradesh states. The collected samples were subjected to standard blotter method and different ochratoxigenic Aspergillus and Penicillium species were isolated and maintained. A multiplex PCR assay was standardized for simultaneous detection of toxigenic Aspergillus and ochratoxin producing Penicillium species targeting pks1, otanps and AflR genes involved in ochratoxin and aflatoxin (AflR) metabolic pathways respectively. An internal amplification control was incorporated into mPCR assay to eliminate the false-positive results during PCR reaction. To check the practical application of developed mPCR assay, a total of 112 cereal grain samples (56 maize and 56 paddy) were used. Out of 56 maize samples 17 had AFB1 positive, 23 had OTA contamination in detectable range. In the case of paddy 22 samples are positive for aflatoxin contamination and 13 were positive for ochratoxin contamination. Similar kind of findings was observed when the pure cultures of fungi were subjected to developed mPCR assay.